2015
DOI: 10.1039/c5dt01444a
|View full text |Cite
|
Sign up to set email alerts
|

Novel La3Fe(MoO4)6 phase: magnetic properties and ethanol reactivity

Abstract: Single crystals of a new oxide, La3Fe(MoO4)6, were grown from fluxes of oxide precursors, and a polycrystalline sample was also prepared by a standard solid state reaction. La3Fe(MoO4)6 crystallizes in the orthorhombic space group Pbca with unit cell parameters a = 19.3164(11), b = 10.4143(5) and c = 22.0594(12) Å. This crystal structure exhibits a singular architectural type built on infinite chains of Fe(MoO4)4, each of them being surrounded by two isolated MoO4 tetrahedra and three isolated La(3+) cations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[54] previously reported that formaldehydea nd CO x were observed with acetaldehyde when am ixture of ethanol/O 2 /He was fed over aF eMoLa catalyst. Colmonte tal.…”
Section: Study Of the Reaction Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…[54] previously reported that formaldehydea nd CO x were observed with acetaldehyde when am ixture of ethanol/O 2 /He was fed over aF eMoLa catalyst. Colmonte tal.…”
Section: Study Of the Reaction Pathwaymentioning
confidence: 99%
“…Colmonte tal. [54] previously reported that formaldehydea nd CO x were observed with acetaldehyde when am ixture of ethanol/O 2 /He was fed over aF eMoLa catalyst. Probably,s ome CH 3 CH(OH)CH 2 COH aldol can be produced over FeMoO x or the aldolization catalyst.…”
Section: Study Of the Reaction Pathwaymentioning
confidence: 99%
“…The crucible was fitted with a platinum lid. It is interesting to note that, due to the refractory behaviour of lanthanum hydroxide, the flux growth technique is often preferred to isolate crystals of novel members [12], [14]. The combined choice of Pb 2+ and La 3+ is governed by their matching within oxo-centered tetrahedra (OPb 4 ) [15] (OBi 4 ) [16], [17] or (OCu 4 ) [18]… The "flexibility" induced by highly polarizable lone pair Pb 2+ species is another key-parameter, this cation being susceptible of sizeable Pb-O distances and the inherent possibility for mixed oxo-centred units, for example in O(Pb,Bi) 4 [19], [20], or O(Pb,Cu) 4 [21].…”
Section: Resultsmentioning
confidence: 99%